Spinal stab injury: A rare injury and individualized management - Ramachandran, Sudheesh; Solanki, Chirag; Bhat, Dhananjaya I.; Indiradevi, Bhagavatula; Sharma, Raman (Indian Journal of Neurotrauma, 2014)
The spinal stab injuries being very rare, there have been no established management guidelines. Our aim is to establish an algorithm for management of this injuries.We in our study report three cases of spinal stab injury which were managed individually. All of them were managed by different modalities of treatment with satisfactory results. Analyzing the different management protocols applied to each case, we try to formulate an algorithm for management of these rare injuries.Out of three cases reported, one of the spinal stab injury patient was managed conservatively as there was no CSF leak. Other patient was managed with CSF diversion as patient had delayed wound CSF leak following wound repair. In contrast our third patient underwent direct primary repair of dural defect as he presented early with CSF wound leak. Analyzing these three patients we propose an algorithm for management of spinal stab injuries.The spinal stab injuries are very rare without established management protocols. In this case series we emphasize on individualized management. The simple algorithm proposed here can be useful in managing spinal stab injuries. A timely appropriate intervention can improve the outcome in spinal stab injury patients and unnecessary interventions can be avoided.
Keywords: Spinal stab injury; CSF leak; CSF diversion; Dural tear; Dural patch repair